Homoeopathy for Warts– A Case Report (Advancements in Homeopathic Research, 2022)
Warts (Verruca) are benign excrescence growth appear on the upper most layer of skin from infection of human papillomavirus (HPV). Since conventional mode of medicine doesn’t completely cure the lesion but suppresses it in the same or the other form, Homoeopathy on the contrary has a significant role in treatment of warts on the basis of individualisation and holistic approach. A case of Filiform warts of 55 years old male is presented in this article who responded commendatory with single dose of Nitricum Acidum 200C depending on totality of symptoms and reportorial result. Reduction in size and number of warts was observed over a period of three months.
Keywords: Filiform warts; Verruca; Nitricum Acidum; homoeopathy; repertorial totality; Single dose